Correction to: Principles of Surgical Treatment of Soft Tissue Sarcomas (Cancers, (2025), 17, 3, (401), 10.3390/cancers17030401) - Gonzalez, Marcos R. (2025)
In the original publication [1], there was a mistake: Table 3 and its citations in the main text were missing. The correct Table 3 and its caption appear below. The citations for Table 3 have been added in 3.1. Margin Assessment. The authors state that the scientific conclusions are unaffected. This correction was approved by the Academic Editor. The original publication has also been updated.